Molecular cloning and characterization of the allatotropin precursor and receptor in the desert locust, Schistocerca gregaria - Lismont, Els; Vleugels, Rut; Marchal, Elisabeth; Badisco, Liesbeth; Van Wielendaele, Pieter; Lenaerts, Cynthia; Zels, Sven; Tobe, Stephen S.; Vanden Broeck, Jozef; Verlinden, Heleen (Frontiers in Neuroscience, 2015)
Allatotropins (ATs) are pleiotropic neuropeptides initially isolated from the tobacco hornworm, Manduca sexta. In 2008, the first receptor for AT-like peptides (ATR) was characterized in Bombyx mori. Since then, ATRs have also been characterized in M. sexta, Tribolium castaneum, Aedes aegypti and Bombus terrestris. These receptors show sequence similarity to vertebrate orexin (ORX) receptors. When generating an EST-database of the desert locust (Schistocerca gregaria) central nervous system, we found cDNA sequences encoding the Schgr-AT precursor and a fragment of its putative receptor. This receptor cDNA has now been completed and functionally expressed in mammalian cell lines. Activation of this receptor, designated as Schgr-ATR, by Schgr-AT caused an increase in intracellular calcium ions, as well as cyclic AMP (cAMP), with an EC50 value in the nanomolar range. In addition, the transcript distribution of both the Schgr-AT precursor and Schgr-ATR was investigated by means of quantitative real-time PCR. Moreover, we found more evidence for the myotropic and allatostimulatory actions of Schgr-AT in the desert locust. These data are discussed and situated in a broader context by comparison with literature data on AT and ATR in insects.